2003
DOI: 10.1097/01.blo.0000063784.32430.b0
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Giant Cell Tumor of Bone: A Case Report and Review of the Literature

Abstract: Multicentric giant cell tumor of bone is the rare variant of a lesion that is relatively common in a skeletally mature population. An otherwise healthy 13-year-old boy presenting with this entity was followed up for 6 years. During this period, the patient was diagnosed with and treated for six individual lesions. One recurrence required resection, Ilizarov bone lengthening, and subsequent ankle arthrodesis. He remains fully active and free of distant metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…In our series as well as in the former literature approximately 1% of GCTB present as multiple synchronous or metachronous lesions (Haskell et al 2003;Hindman et al 1994;Hoch et al 2006;Leggon et al 2004;Taraporvala et al 1997;Taylor et al 2003). As reported by several authors, patients with multicentric GCTB are likely to be younger than those with a solitary lesion (Hindman et al 1994;Hoch et al 2006).…”
Section: Multifocal Gctbsupporting
confidence: 53%
“…In our series as well as in the former literature approximately 1% of GCTB present as multiple synchronous or metachronous lesions (Haskell et al 2003;Hindman et al 1994;Hoch et al 2006;Leggon et al 2004;Taraporvala et al 1997;Taylor et al 2003). As reported by several authors, patients with multicentric GCTB are likely to be younger than those with a solitary lesion (Hindman et al 1994;Hoch et al 2006).…”
Section: Multifocal Gctbsupporting
confidence: 53%
“…[67] Half-yearly screening by either bone scan or skeletal survey is recommended for GCTs at unusual sites or those diagnosed with multicentric involvement. Our literature review [Table 1] showed that this protocol should be followed for at least five years, as most cases develop multicentricity and additional lesions within this period.…”
Section: Discussionmentioning
confidence: 99%
“…Multicentric GCTs are extremely rare and represent less than 1% of GCTs [32]. Fewer than 60 cases have been reported in the literature [2,3,7,8,9,10,11,12,13,14,15,16,17,19,20,21,22,23,24,25,26,27,29,30,31,33,35,36]. Therefore, the pathogenesis of multiple benign lesions is still a matter of debate [22].…”
Section: Introductionmentioning
confidence: 98%